1979
DOI: 10.1093/ajcn/32.7.1511
|View full text |Cite
|
Sign up to set email alerts
|

Dietary zinc intake of low-income pregnant women of Mexican descent

Abstract: Zinc intakes of low-income pregnant women of Mexican descent were estimated by the use of 24-hr dietary recalls. Recalls were obtained during the first two trimesters for 344 women and again during the third trimester of pregnancy for 279 of the same women. The daily mean zinc intake was calculated as 9.4 +/- 3.8 mg during the first two trimesters and as 10.0 +/- 4.3 mg during the third trimester. For about 85% of the women, the reported intakes were below two-thirds of the Recommended Dietary Allowance for zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…The low plasma or serum Zn levels during pregnancy have been observed for a long time [1][2][3][4][5][9][10][11][12][13][14][15][17][18][19]22,24,25,27,30,31]. This decline has been considered as physiological phenomenon and attributed to such factors as an increase in plasma volume, changes in albumin-Zn affinity, and hormonal influences by some authors [2,13,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The low plasma or serum Zn levels during pregnancy have been observed for a long time [1][2][3][4][5][9][10][11][12][13][14][15][17][18][19]22,24,25,27,30,31]. This decline has been considered as physiological phenomenon and attributed to such factors as an increase in plasma volume, changes in albumin-Zn affinity, and hormonal influences by some authors [2,13,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, several investigators have observed an association between low maternal plasma/serum Zn concentration and pregnancy outcomes [1,3,[5][6][7][8][9][10][11]24,25,27,30,31]. On the other hand, it has been shown by us and others that a close association between plasma, serum Zn levels and nutrition exists during pregnancy (3,4,12,15,16,18,19,22,24,25,(27)(28)(29)(30)32). This longitudinal study once more has demonstrated that poor nutrition adversely affects plasma Zn levels, a finding that runs parallel to those of our two previous cross-sectional studies in pregnant Turkish women [4,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soldados americanos tinham uma ingestão média de zinco, diá-ria, de 20.3mg (Milne, et al, 1978). Mulheres grávidas mexicanas de baixa renda 10.0 mg por dia (Hunt, et al, 1978). Adolecentes americanos do sexo feminino 11.3 mg diárias (Greger, et al, 1978).…”
Section: Discussionunclassified